An eclectic bestiary : encounters in a more-than-human world - Spengler, Birgit; Tischleder, Babette Bärbel, 1968- (Transcript Verlag, 2019)
"The essays, poetry, and visual art collected here consider the more-than-human cultures of our multispecies world. At a time when humanity's impact has put our planet's ecosystems into great jeopardy, the book explores literary, sonic, and visual imaginaries that feature encounters between and across a variety of living creatures: beetles and bisons, people and pigeons, trees and spiderwebs, vegetables and violets, orchards and octopi, vampires and tricksters. Offering a wide range of critical and creative contributions to Human Animal Studies, Critical Plant Studies and the Nonhuman Turn, the volume seeks to foster new ways of imagining a more "response-able" coexistence on our shared Earth."-- Provided by publisher
Keywords: Human-animal relationships in art.; Human-animal relationships.; Animals in art.; Plants in art.; Relations homme-animal dans l'art.; Relations humain-animal.; SOCIAL SCIENCE -- General.; SOCIAL SCIENCE / General; Animals in art; Human-animal relationships; Human-animal relationships in art; Plants in art; Animal History.; Animal Studies.; Animal.; Anthropocene.; Critical Plant Studies.; Cultural Studies.; Culture.; Human.; Literary Studies.; Nonhuman Studies.; North American Ecocriticism.; Photography.; Posthumanism.; Electronic books.